2002
DOI: 10.1046/j.1471-5740.2002.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Food services trends in New South Wales hospitals, 1993–2001

Abstract: A survey of the food service departments in 93 hospitals throughout NSW Australia (covering 51% of hospital beds in the state) was conducted using a mailed questionnaire and the results compared with those from similar surveys conducted in 1986 and 1993. Over the past eight years there has been a significant increase in the proportion of hospitals using cook‐chill food service production systems, from 18% in 1993 to 42% in 2001 (P < 0.001). Hospitals with cook‐chill systems had better staff ratios than those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 9 publications
4
35
0
Order By: Relevance
“…This might be a better option than a complete shift toward a new system due to the savings that could occur in the area of capital cost. The result of the cook-chill system is also promising, in line with previous studies by Light and Walker (1990), Clark (1997) and Mibey and Williams (2002), and it also supports theories by Synder (1983) and Stewart (1985) who stressed the importance of cook-chill production systems to increase productivity. The result, however, is not consistent with those from the study by Greathouse (1987) which found, that managers of traditional and cook-chill systems are employing similar resources to achieve their objectives.…”
Section: Resultssupporting
confidence: 88%
“…This might be a better option than a complete shift toward a new system due to the savings that could occur in the area of capital cost. The result of the cook-chill system is also promising, in line with previous studies by Light and Walker (1990), Clark (1997) and Mibey and Williams (2002), and it also supports theories by Synder (1983) and Stewart (1985) who stressed the importance of cook-chill production systems to increase productivity. The result, however, is not consistent with those from the study by Greathouse (1987) which found, that managers of traditional and cook-chill systems are employing similar resources to achieve their objectives.…”
Section: Resultssupporting
confidence: 88%
“…In particular the evening meals are usually served quite early, so there can be a long period of time overnight without food. In two Australian surveys in 1993 and 2001 it was reported most hospitals began serving the breakfast meal between 7am and 8am, the midday meal was served between 12.00 noon to 12.30pm, and the evening meal times were spread over two and a half hours from 3.30pm to 6.00pm with most meal service being between 5.00pm and 5.30pm (Mibey and Williams, 2002). Similar meal times can be seen in hospitals in the US and the UK.…”
Section: Timing Of Meals In Institutionsmentioning
confidence: 81%
“…They can be an important occasion at which to increase the nutritional intake of vulnerable clients who may have poor appetites and they can provide more than a quarter of the daily energy intake of patients (Walton et al, 2007). One Australian survey found that most hospitals regularly provided patients with three midmeals: 98% served morning tea, 99% served afternoon tea, and 95% served supper, and 19% even offered a pre-breakfast early morning hot beverage (Mibey and Williams, 2002).…”
Section: Supplementary Feedingmentioning
confidence: 99%
“…A study by the NSW Health Department in 1996, for example, indicated that only 78% foodservice managers in NSW are qualified at all. Mibey and Williams (2002) also assessed the qualification of the head of the foodservice department in NSW hospitals. Their results showed that 60% of managers were without formal qualification in the smaller hospitals (5100 beds) and only 44% of managers had qualifications in larger hospitals.…”
Section: Second Stage Resultsmentioning
confidence: 99%